Segmental facial infantile haemangiomas in the era of propranolol: evaluation at 6 years of age. (12th January 2022) - Letertre, O.; Boccara, O.; Prey, S.; Pedespan, J.‐M.; Boralevi, F.; Léauté‐Labrèze, C.
Abstract: Background: The long‐term evolution of children with segmental facial infantile haemangioma (SFIH) treated with propranolol remains unstudied. Objectives: The objective of this study was to evaluate the neurodevelopmental features of children with SFIH treated with propranolol at 6 years of age. Methods: This retrospective case series study was conducted from January 2008 to June 2020 using data from medical files, patient examinations and appointments spanning 6 years. To be included, patients should present SFIH and have previously received propranolol. A complete physical examination, magnetic resonance imaging (MRI) of the head, echocardiography and ophthalmologic examination should have been performed. Neurodevelopmental features were divided into cognition, audition, vision, orality, motor skills and the occurrence of new symptoms. Results: Thirty children with SFIH were included. Of these, 11 presented criteria of PHACES. Evaluation of neurodevelopmental features of the children at 6 years of age showed learning difficulties in one case but grade skipping in three cases. There were six cases of unilateral hearing loss that had not been diagnosed at birth, two of oral difficulties and one of minor hypotonia. Early headache was primarily reported as the main new outcome. All children were treated with propranolol, with three following oral steroid therapy. No severe adverse effects were reported. The median length of treatment with propranolol was 16 months, and the median age at treatment cessation was 21 months. Analysis based on segment implication showed the median length of treatment to vary from 12 months (if S3 was spared) to 25 months (if at least S3 was involved). Vascular laser therapy was used in 16 patients (53.3%) and surgery in four. Conclusion: In this case series, children with SFIH, including patients with PHACES criteria, presented a good tolerance of propranolol, as well as encouraged neurodevelopmental data. Segmental implication appears to have a significant impact on treatment duration and associated complications. Abstract : Linked Commentary: C. Gelmetti J Eur Acad Dermatol Venereol 2022; 36 : 492–493. https://doi.org/10.1111/jdv.18002 .